Contestation Of Political Economy Interests in Artisanal Mining (Comparative Study Of Jambi Province And Bangka Belitung Province) - Darminto, Citra; Arif Rahman, Moh; Karim, Navarin (LPPM Universitas Jambi, 2025)
This research aims to uncover and analyze the complex conflicts of interest in artisanal mining activities in Jambi and Bangka Belitung provinces. Although mining has long been the backbone of the economy in these two regions, its rapid growth has caused various problems. Environmental damage and social conflicts involving various parties are inevitable impacts. The focus of this research is on artisanal mining areas (WPR) in both provinces. Using a qualitative-comparative method, this research will identify and analyze four main aspects: competing economic and political interests, the dynamics of conflicts of interest, the impact on community welfare, and existing mining management policies. Primary and secondary data will be collected and analyzed using the Miles and Huberman method to deeply understand the phenomenon of conflict of interest in the context of artisanal mining. The results of this research are expected to contribute to the development of better policies in sustainably managing community mining activities. The expected outputs of this research are scientific publications in reputable international journals, presentations at international conferences, and the preparation of public policies that can be a reference for relevant stakeholders.